TEKNIK SURVEI SITUS TERBUKA - Tjahjono, Baskoro Daru (BRIN, 2000)
In this paper, it is hoped that this does not merely present survey techniques on open sites which may have been discussed by many experts and have been applied to archaeological researches in Indonesia. However, it is also hoped that they will be able to find alternatives to the application of appropriate survey techniques for an archaeological research. For this reason, it is suggested that there are specific themes in archaeological research, so that it is not just artefactual research.